The The Challenge of Using the Transcendental Principle in the Law of Marriage in Indonesia - Sanjaya, Umar Haris; Rohidin, Rohidin; Ummah, Karimatul (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
Marriage law in Indonesia is a law based on God. This divine basis is applied in Article 1 of Law Number 1 of 1974 on Marriage that marital relations are based on the belief in the One and Only God. In practice, this is overlooked when it comes to law enforcement in court applications. The waiver has the potential to occur if it is related to interfaith marriages/marriages between religions and beliefs in court, lack of public knowledge, or is considered a violation of the right to marry. Remembering that marriage is one's privacy. This article aims to analyze the transcendental principle in Law Number 1 of 1974 on Marriage and to elaborate the enforcement of the transcendental principle in court. This article uses the methodology juridical and normative research, which means that research is using principle of law and doctrine to answer the legal issues. This results show that the practice of transcendental principle is the nature of God Almighty, so every marriage must be based on this principle. Another finding, there are attempts to change this principle through judicial review but are always rejected by the court in Constitutional Court. Transcendental principle has not been able to answer the needs of each society individually. It is because there are still people who ignore this principle.